Causes, presentation and outcome of lesional adult onset mediotemporal lobe epilepsy. Issue 8 (8th April 2009) - Soeder, B M; Gleissner, U; Urbach, H; Clusmann, H; Elger, C E; Vincent, A; Bien, C G
Abstract : Background and aim: Mediotemporal lobe (MTL) epilepsy (MTLE) is particularly frequent among human localisation related epilepsies. MTLE usually starts before adulthood and is most frequently associated with hippocampal sclerosis (HS). Here, aetiologies, disease courses and outcomes of adult onset MTLE patients treated at this tertiary epilepsy centre are studied. Methods: We collected all patients studied between January 1999 and December 2005 fulfilling the following criteria: (1) MTLE manifestation at age >20 years; (2) time between disease manifestation and assessment ⩽6 years; (3) MTL lesion on brain MRI; and (4) neuropsychological test battery applied. The diagnoses were classified and paraclinical data, neuropsychological performances, and seizure and memory outcomes were documented. Results: Diagnoses in the 84 patients (mean age 42 years at MTLE onset) were: limbic encephalitis (LE), n = 23 (27%); HS (unrelated to inflammation), n = 18 (22%); tumours I/II°, n = 12 (14%); amygdala lesions (increased volume and T2/FLAIR signal), n = 11 (13%); and other, n = 20 (24%). Visible MTL affection was frequently bilateral in patients with LE (57%) and HS (22%). These groups also showed the poorest memory performance. Patients with amygdala lesions were the oldest (mean age 52 years); their lesions were in part immune mediated and in part probably dysplastic. Treatment dependent seizure outcomes were similar to published data without restriction to adult onset cases. Under conservative therapy, memory performance remained stable in patients with HS but improved in a proportion of patients with LE. Conclusions: The data suggest that LE is a common and a previously underestimated cause of MTLE in this age group. Its prognosis is variable. Amygdala lesions, also, are in part encephalitic in nature.